2010
DOI: 10.1111/j.1365-2966.2010.16539.x
|View full text |Cite
|
Sign up to set email alerts
|

Abundances and search for vertical stratification in the atmospheres of four HgMn stars

Abstract: Using high‐resolution, high‐signal‐to‐noise ratio archival UVES (Ultraviolet‐Visual Echelle Spectrograph) spectra, we have performed a detailed spectroscopic analysis of four chemically peculiar HgMn stars (HD 71066, HD 175640, HD 178065 and HD 221507). Using spectrum synthesis, mean photospheric chemical abundances are derived for 22 ions of 16 elements. We find good agreement between our derived abundances and those published previously by other authors. For the five elements that present a sufficient number… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…The comparison with the abundances by Thiam et al (2010) has shown close agreement between the two determinations. Because Thiam et al (2010) use an ATLAS9 model computed for solar abundances, the ATLAS12 model computed for an individual abundance may be estimated as unnecessary.…”
Section: Model Parameters and Abundances Of Hd 71066supporting
confidence: 48%
See 3 more Smart Citations
“…The comparison with the abundances by Thiam et al (2010) has shown close agreement between the two determinations. Because Thiam et al (2010) use an ATLAS9 model computed for solar abundances, the ATLAS12 model computed for an individual abundance may be estimated as unnecessary.…”
Section: Model Parameters and Abundances Of Hd 71066supporting
confidence: 48%
“…Previous studies of HD 71066 (κ 2 Vol, HR 3302) have pointed out the isotopic anomaly of Hg (Dolk et al 2003;Thiam et al 2010). No vertical abundance stratification for Ti, Cr, and Fe is found by Thiam et al (2010).…”
Section: The Hgmn Star Hd 71066mentioning
confidence: 96%
See 2 more Smart Citations
“…Although there is no compelling observational evidence of this phenomenon in HgMn stars (Savanov & Hubrig 2003;Thiam et al 2010;Makaganiuk et al 2012), an accumulation at different layers is supported by theoretical calculations (Sect. 4).…”
Section: Fundamental Parameters and Chemical Compositionmentioning
confidence: 83%